Ankle-brachial index and subclinical atherosclerosis in type 1 diabetes - Lima,Alexandra Corrêa Gervazoni Balbuena de (2021)
SUMMARY OBJECTIVE: To assess the prevalence of altered ankle-brachial index (<0.9 or >1.3) in patients with type 1 diabetes and to compare it with the presence of subclinical atherosclerosis by carotid ultrasound. METHODS: Prospective, cross-sectional study in which 45 adults with type 1 diabetes were evaluated (age 34±10 years, 46.7% men). The data collected included anamnesis, clinical evaluation, calculation of the ankle-brachial index (relationship between systolic blood pressure in the ankle and brachial artery), and performance of carotid ultrasound. RESULTS: Thirty-two patients had ankle-brachial index >1.3 (66.7%) and no patient had ankle-brachial index <0.9. Carotid echocardiography was performed on 21 patients, 4 (19%) of whom had atherosclerosis. Age >35 years and ankle-brachial index >1.4 showed a good correlation with atherosclerosis (r=0.49, p=0.021; r=0.56, p=0.008, respectively). A model associating age >35 years and ankle-brachial index >1.4 showed an excellent relationship with atherosclerosis (r=0.59, p=0.004). CONCLUSIONS: Our study showed that vascular calcification (ankle-brachial index >1.4) was frequent in this population with type 1 diabetes and associated with subclinical atherosclerosis. A model combining ankle-brachial index >1.4 and age >35 years showed an excellent correlation with atherosclerosis and can assist in clinical suspicion and optimize the request for additional tests.